Предмет: Алгебра,
автор: ElinaN26
Помогите пожалуйста! Упростите выражение:
а) (х-2)(3+х)-(х-1)²
б) (7+6а)(6а-7)
Заранее спасибо))
Ответы
Автор ответа:
1
Это 100 процентов правильно)
Приложения:
Автор ответа:
1
(x-2)(3+x)-(x-1)^2=3x-6+x^2-2x-x^2+2x-1=3x-7
(7+6a)(6a-7)=36a^2-49
(7+6a)(6a-7)=36a^2-49
Похожие вопросы
Предмет: Английский язык,
автор: Аноним
Предмет: История,
автор: lyashin3395
Предмет: Қазақ тiлi,
автор: salosalemkosh
Предмет: Алгебра,
автор: нагибатор3
Предмет: Физика,
автор: Аноним